Can inspiratory muscle training improve weaning outcomes in difficult to wean patients? A protocol for a randomised controlled trial (IMweanT study). Issue 6 (30th June 2018) - Hoffman, Mariana; Van Hollebeke, Marine; Clerckx, Beatrix; Muller, Johannes; Louvaris, Zafeiris; Gosselink, Rik; Hermans, Greet; Langer, Daniel
Abstract : Introduction: Respiratory muscle dysfunction has been associated with failure to wean from mechanical ventilation. It has therefore been hypothesised that these patients might benefit from inspiratory muscle training (IMT). Evidence, however, is thus far limited to data from small, single-centre studies with heterogeneity in inclusion criteria, training modalities and outcomes. The aim of this study is to evaluate the effects of a novel IMT method on weaning outcomes in selected patients with weaning difficulties. Methods: This study is designed as a double-blind, parallel-group, randomised controlled superiority trial with 1:1 allocation ratio. Patients with weaning difficulties will be randomly allocated into either an IMT group (intervention) or a sham-IMT group (control). Ninetypatients (45 in each group) will be needed to detect a 28% difference in the proportion of weaning success between groups (estimated difference in primary outcome based on previous studies) with a risk for type I error (α) of 5% and statistical power (1-β) of 80%. Patients will perform four sets of 6–10 breaths daily against an external load using a tapered flow resistive loading device (POWERbreathe KH2, HaB International, UK). Training intensity in the intervention group will be adjusted to the highest tolerable load. The control group will train against a low resistance that will not be modified during the training period. Training will becontinued until patients are successfully weaned or for a maximum duration of 28 days. Pulmonary and respiratory muscle function, weaning duration, duration of mechanical ventilation, ventilator-free days and length of stay in the intensive care unit will be evaluated as secondary outcomes. Χ2 tests and analysis of covariance with adjustments for baseline values of respective outcomesas covariates will be used to compare results after the intervention period between groups. Ethics and dissemination: Ethics approval was obtained from the local ethical committee (Ethische Commissie Onderzoek UZ/KU Leuven protocol ID: S60516). Results from this randomised controlled trial will be presented at scientific meetings as abstracts for poster or oral presentations and published in peerreviewed journals. Trial status: Enrolment into the study have started in August 2017. Data collection and data analysis are expected to be completed in September 2021. Trial registration number: NCT03240263 .